Diminished production of T helper 1 cytokines correlates with T cell unresponsiveness to Brucella cytoplasmic proteins in chronic human brucellosis - Giambartolomei, Guillermo Hernan (2002)
This study evaluated the cellular immune response against Brucella species cytoplasmic protein (CP) in peripheral blood mononuclear cells (PBMC) of 25 patients with brucellosis. In vitro proliferation and cytokine gene expression and production were investigated. PBMC from 14 patients proliferated in response to CP (responder patients [RPs]) and cells from 11 patients did not (nonresponder patients [NRPs]). CP-specific interleukin (IL)-2 and interferon-γ were significantly induced in PBMC from RPs, compared with cells from NRPs. No significant differences were found in the production of IL-10 between the 2 groups. CP did not induce IL-4 production. A close relationship was observed between the clinical status of the patients and the T cell response against CP. Patient with acute infections responded to CP and induced production of T helper 1 (Th1) cytokines, whereas chronically infected patients did not. Diminished production of Th1 cytokines may contribute to T cell unresponsiveness in chronic human brucellosis.